Lattice strained CuO electrocatalyst and its preparation method and application

By preparing lattice strained CuO electrocatalyst in glycerol electrooxidation system, using Cu+/Cu2+ reversible redox pairs to reduce the initial oxidation potential of glycerol electrooxidation, the high energy consumption and glycerol electrooxidation reaction efficiency in the preparation of hydrogen electrolytic water are solved. The problem of low efficiency of electrolysis and catalyst regeneration is achieved.

CN118581493BActive Publication Date: 2024-12-24INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411068382.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-24
Estimated Expiration
2044-08-06

AI Technical Summary

Technical Problem

The thermodynamic potential of the oxygen evolution reaction in the preparation of hydrogen electrolytic water is high, resulting in large energy consumption, and the actual oxidation potential of the glycerol electrooxidation reaction significantly exceeds the thermodynamic reaction potential, which is low efficiency and makes it difficult to develop a catalyst with low overpotentiality.

Method used

Preparation of lattice strained CuO electrocatalysts by adding Cu salt to the alkaline glycerol electrooxidation system to form a copper glycerol complex, and in situ generates CuO on foam nickel or carbon paper electrodes to achieve Cu+/Cu2+ reversible redox pairs, reducing The initial oxidation potential of glycerol electrooxidation.

Benefits of technology

It effectively reduces the overpotential of glycerol electrooxidation reaction, improves electrolytic efficiency, significantly reduces energy consumption, and realizes in-situ regeneration of catalysts, with industrial potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118581493B_ABST
    Figure CN118581493B_ABST
Patent Text Reader

Abstract

The present invention discloses a lattice strained CuO electrocatalyst and its preparation method and application, belonging to the field of electrochemical synthesis and catalysis technology. The preparation method of the lattice strained CuO electrocatalyst is as follows: Cu salt is added to a glycerol electro-oxidation reaction cell to form a glycerol copper soluble complex. During the glycerol electro-oxidation process, CuO can be generated in situ on the anode surface of nickel foam, carbon paper, etc. (this CuO lattice contains about 1.7% compressive strain, so it is named lattice strained CuO). The indirect oxidation mechanism of lattice strained CuO significantly reduces the initial oxidation potential of glycerol, which is of great significance to reducing the energy consumption of glycerol electro-oxidation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical synthesis and catalysis, and in particular to a method for preparing a lattice strained CuO electrocatalyst and application thereof in glycerol electrooxidation. Background Art

[0002] Hydrogen plays a key role in the conversion of renewable energy. Hydrogen production by water electrolysis is a promising method for producing green hydrogen. However, the oxygen evolution reaction (OER) at the anode of water electrolysis has an inherent defect of high thermodynamic potential (1.23V RHE ), resulting in a large amount of energy consumption, which hinders the widespread application of hydrogen production by water electrolysis. Glycerol is a by-product in the production of biodiesel. For every ton of biodiesel produced, 100 kg of glycerol is produced. At present, the annual surplus of glycerol exceeds 1 million tons. By electro-oxidizing glycerol, chemicals with higher added value, such as glyceric acid, glycolic acid and formic acid, can be obtained. In addition, the glycerol electro-oxidation reaction (GOR) has a low thermodynamic potential (0.69 V RHE ), is an ideal alternative OER reaction. Nevertheless, the actual oxidation potential of GOR still significantly exceeds its thermodynamic reaction potential, resulting in low efficiency. Therefore, reducing the overpotential of GOR is crucial to improving electrolysis efficiency and reducing energy consumption.

[0003] The overpotential of GOR depends mainly on the onset oxidation potential, which is closely related to the redox potential of the catalyst used. Among the widely studied catalysts, such as nickel-based, cobalt-based, and copper-based catalysts, the onset oxidation potential of GOR is related to Ni, 2+ / Ni 3+ 、Co 2+ / Co 3+ and Cu 2+ / Cu 3+ These redox potentials are usually intrinsic to the catalytic material and are relatively high (e.g., Ni 2+ / Ni 3+ , about 1.35 V RHE ). It is difficult to significantly reduce these redox potentials by doping or other modification methods. This poses a major challenge to the development of GOR catalysts with low overpotentials.

[0004] We prepared a lattice-strained CuO catalyst. Different from conventional CuO, in this catalyst, the Cu + / Cu 2+ The reversible redox couple indirectly electrooxidized glycerol, reducing the onset oxidation potential of GOR to 0.9 V RHE , effectively reducing the GOR reaction overpotential. Summary of the invention

[0005] The present invention is directed to a method for preparing a lattice strained CuO electrocatalyst and its application in glycerol electrooxidation. In the anode reaction chamber of the glycerol electrooxidation reaction, a Cu salt is added to form a glycerol copper complex. During the reaction, CuO is generated in situ on electrodes such as nickel foam and carbon paper. + / Cu 2+ Reversible redox couple can realize indirect electrooxidation of glycerol.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The invention discloses a method for preparing a lattice strained CuO electrocatalyst. In an alkaline glycerol electro-oxidation system, a Cu salt is added to an anode chamber to obtain an electrolyte containing a glycerol copper complex, and one or more conductive substrates such as nickel foam or carbon paper are used as electrodes. Electrolysis is performed at a given potential for a certain period of time to obtain a lattice strained CuO electrocatalyst supported on the conductive substrate.

[0008] Further, the pH of the alkaline glycerol electro-oxidation system is ≥13 (preferably ≥14, more preferably 14), which is an alkaline aqueous solution of one or more of KOH, NaOH, and LiOH;

[0009] The Cu salt is one or more of CuSO4, Cu(NO3)2, and CuCl2, and the concentration of the Cu salt is 0.01-0.05 mol / L (preferably 0.03-0.05 mol / L, more preferably 0.05 mol / L);

[0010] The concentration of glycerol in the alkaline aqueous solution is 0.05 to 0.5 mol / L (preferably 0.05 to 0.2 mol / L, more preferably 0.1 mol / L).

[0011] Furthermore, the glycerol electrooxidation reaction is carried out in an H-type electrolytic cell separated by a proton exchange membrane; a three-electrode system is adopted, the working electrode and the reference electrode are placed in the anode reaction chamber, the counter electrode is placed in the cathode reaction chamber, the reference electrode is mercury / mercuric oxide, and the counter electrode is a graphite rod;

[0012] Cu salt is added into the anode chamber to obtain an electrolyte containing glycerol copper complex, and the electrolyte in the cathode chamber is an alkaline aqueous solution of one or more of KOH, NaOH and LiOH with a pH value of ≥13.

[0013] Furthermore, the lattice strained CuO electrocatalyst preparation process uses a constant voltage electrolysis process: the ratio of the area of ​​the anolyte to the working electrode is 10-30 mL / cm 2 (Preferably 10~20 mL / cm 2, more preferably 12~15 mL / cm 2 );

[0014] After the reaction, the lattice strained CuO loading on the electrode is 0.5 mg to 10 mg (preferably 1 to 9 mg, more preferably 3 to 7 mg).

[0015] Furthermore, the lattice strained CuO preparation process should be carried out at 1.65~1.95 V RHE (Preferably 1.7~1.8 V RHE , preferably 1.75 V RHE ) for 0.5 to 1 hour (preferably 0.5 to 0.7 hours, more preferably 0.5 hour).

[0016] Furthermore, the preparation method can obtain a lattice-strained CuO electrocatalyst.

[0017] Furthermore, the lattice strained CuO electrocatalyst is used in the electro-oxidation of glycerol, and the lattice strained CuO electrocatalyst is used to electro-oxidize glycerol in an alkaline glycerol electro-oxidation system.

[0018] Further, the pH of the alkaline glycerol electro-oxidation system is ≥13 (preferably ≥14, more preferably 14), which is an alkaline aqueous solution of one or more of KOH, NaOH, and LiOH;

[0019] The glycerol concentration in the alkaline aqueous solution is 0.05-0.5 mol / L (preferably 0.05-0.2 mol / L, more preferably 0.1 mol / L);

[0020] The initial oxidation potential of glycerol (0.9 V RHE ) is significantly lower than conventional CuO (1.13 V RHE ).

[0021] The preparation method of the lattice strained CuO electrocatalyst is as follows: Cu salt is added to a glycerol electrooxidation reaction cell to form a glycerol copper soluble complex, and during the glycerol electrooxidation process, CuO can be generated in situ on the anode surface of nickel foam, carbon paper, etc. (this CuO lattice contains about 1.7% compressive strain, so it is named lattice strained CuO). The indirect oxidation mechanism of lattice strained CuO significantly reduces the initial oxidation potential of glycerol, which is of great significance to reducing the energy consumption of glycerol electrooxidation.

[0022] The principle of the present invention is as follows:

[0023] The in-situ generation of CuO on conductive substrates such as nickel foam and carbon paper using the glycerol electrooxidation process has a special performance of indirect electrooxidation of glycerol. Specifically, the high potential of the anode releases the lattice strain, and at the same time, the Cu in CuO +Oxidation to Cu 2 + , the generated Cu 2+ Can be reduced to Cu by glycerol + , while glycerol is oxidized. This indirect electrooxidation mechanism is the source of the excellent catalytic performance of lattice-strained CuO.

[0024] The advantages of the present invention are as follows:

[0025] 1. The present invention can unify the electrolysis process and the preparation process, omitting the complicated catalyst preparation process. At the same time, this feature can be used to realize in-situ catalyst regeneration, which has industrial prospects and potential.

[0026] 2. The special catalytic mechanism of the lattice strained CuO described in the present invention enables it to have excellent glycerol electro-oxidation performance, which is significantly better than conventional CuO catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It curve of the process of growing lattice strained CuO on nickel foam (NF).

[0028] Figure 2 XRD patterns of lattice strained CuO and its annealed samples.

[0029] Figure 3 High-resolution transmission electron microscope images of lattice strained CuO and its annealed samples.

[0030] Figure 4 Cyclic voltammetry curves of lattice strained CuO and its annealed samples (tested in electrolytes with and without glycerol, respectively).

[0031] Figure 5 High-resolution transmission electron microscopy images of the lattice strained CuO sample before and after the reaction. DETAILED DESCRIPTION

[0032] Embodiment 1:

[0033] The preparation of lattice strained CuO is carried out during the electro-oxidation of glycerol. Taking the synthesis of lattice strained CuO on nickel foam (NF) as an example, the specific method is as follows: in a three-electrode system, the washed nickel foam (length * width * thickness = 1 cm * 1 cm * 0.15 cm) is used as the working electrode, the graphite rod is used as the counter electrode, and the mercury / mercury oxide reference electrode is used. An H-type electrolytic cell is used, the working electrode and the reference electrode are placed in the anode reaction chamber, and the counter electrode is placed in the cathode reaction chamber. The electrolyte has a pH of 14.0, the electrolyte in the anode chamber is 15 mL of 1 mol / L KOH + 0.1 mol / L glycerol + 0.05 mol / L CuSO4 solution, and the electrolyte in the cathode chamber is 15 mL of 1 mol / L KOH solution. The anode and cathode reaction chambers are separated by a Nafion proton membrane (subsequent electrochemical experiments are all carried out in this three-electrode system). At 1.75 V RHE The ratio of the anolyte to the working electrode area was 15 mL / cm 2 The it curve of the electrolysis process is as follows Figure 1 As shown in the figure, the increase in current density is due to the excellent catalytic performance of glycerol electrooxidation of the lattice strained CuO grown on the surface of nickel foam during electrolysis. The subsequent decrease in potential is due to the decrease in concentration of glycerol consumed in the anode reaction chamber. After electrolysis, lattice strained CuO (CuO-LS) supported on nickel foam was obtained. The amount of lattice strained CuO loaded on the surface of nickel foam was 4.5 mg cm-1 obtained by the change in electrode weight before and after the reaction. -2 .

[0034] Example 2

[0035] The preparation of lattice strained CuO is carried out during the electro-oxidation of glycerol. Taking the synthesis of lattice strained CuO on nickel foam (NF) as an example, the specific method is: in a three-electrode system, the washed nickel foam (length * width * thickness = 1 cm * 1 cm * 0.15 cm) is used as the working electrode, the graphite rod is used as the counter electrode, and the mercury / mercury oxide reference electrode is used. An H-type electrolytic cell is used, the working electrode and the reference electrode are placed in the anode reaction chamber, and the counter electrode is placed in the cathode reaction chamber. The electrolyte in the cathode chamber has a pH of 13.0, the electrolyte in the anode chamber is 10 mL of 1 mol / L KOH +0.05mol / L glycerol + 0.01 mol / L CuSO4 solution, and the electrolyte in the cathode chamber is 15 mL of 1 mol / L KOH solution. The anode and cathode reaction chambers are separated by a Nafion proton membrane (subsequent electrochemical experiments are all carried out in this three-electrode system). At 1.65 V RHE The ratio of the anolyte area to the working electrode area was 10 mL / cm 2The amount of lattice strain CuO loaded on the surface of nickel foam was obtained by the change in electrode weight before and after the reaction, which was 0.5 mg cm -2 .

[0036] Example 3

[0037] The preparation of lattice strained CuO is carried out during the electro-oxidation of glycerol. Taking the synthesis of lattice strained CuO on nickel foam (NF) as an example, the specific method is as follows: in a three-electrode system, the washed nickel foam (length * width * thickness = 1 cm * 1 cm * 0.15 cm) is used as the working electrode, the graphite rod is used as the counter electrode, and the mercury / mercury oxide reference electrode is used. An H-type electrolytic cell is used, the working electrode and the reference electrode are placed in the anode reaction chamber, and the counter electrode is placed in the cathode reaction chamber. The electrolyte in the cathode chamber has a pH of 14.3, the electrolyte in the anode chamber is 30 mL of 1 mol / L KOH + 0.5mol / L glycerol + 0.03 mol / L CuSO4 solution, and the electrolyte in the cathode chamber is 15 mL of 1 mol / L KOH solution. The anode and cathode reaction chambers are separated by a Nafion proton membrane (subsequent electrochemical experiments are all carried out in this three-electrode system). At 1.95 V RHE The ratio of the anolyte to the working electrode area was 30 mL / cm 2 The amount of lattice strain CuO loaded on the surface of nickel foam was obtained by the change in electrode weight before and after the reaction, which was 10 mg cm -2 .

[0038] Example 4

[0039] Since the annealing process can release the strain in the material, XRD and TEM tests were performed on the lattice strained CuO (CuO-LS) prepared in Example 1 and the lattice strained CuO (CuO-LS) prepared in Example 1 after annealing at 400°C for 5 hours. The XRD results are shown in Figure 2 As shown in the figure, both the lattice strained CuO and the annealed sample show the crystal structure of CuO. In addition, the diffraction angle of the (111) crystal plane in the lattice strained CuO sample moves to a higher angle than that of the annealed sample, indicating that the lattice strained CuO has a certain lattice compressive strain compared to the annealed sample. Figure 3 As shown in the figure, the lattice strained CuO has a smaller interplanar spacing than the annealed sample (lattice strained CuO is 0.227nm, and its retreated sample is 0.231 nm), indicating that the lattice strained CuO sample contains about 1.7% lattice compressive strain relative to its retreated sample (reference: Science 2016, 354, 6315, 1031-1036.), which further confirms the XRD results. And the existence of lattice strain can be more intuitively seen from the original lattice fringe diagram.

[0040] Example 5

[0041] The lattice strained CuO sample (CuO-LS) prepared in Example 1 was subjected to cyclic voltammetry (from 0.36 V RHE Sweep to 1.21 V RHE , scan rate is 0.01 V / s).

[0042] In the three-electrode system, the lattice strained CuO sample prepared in Example 1 was used as the working electrode, the graphite rod was used as the counter electrode, and the mercury / mercuric oxide reference electrode was used. An H-type electrolytic cell was used, the working electrode and the reference electrode were placed in the anode reaction chamber, the counter electrode was placed in the cathode reaction chamber, the electrolyte in the anode chamber was 15 mL of the following solution, and the electrolyte in the cathode chamber was 15 mL of 1 mol / L KOH solution. The cathode and cathode reaction chambers were separated by a Nafion proton membrane.

[0043] The reaction conditions are: the dotted line is 1 mol / L KOH electrolyte; the solid line is 1 mol / L KOH + 0.1 mol / L glycerol electrolyte; the electrolyte volume is 15 mL. Figure 4 As shown in the lower part of the figure, the voltage is greater than 0.9 V RHE Cu + / Cu 2+ The redox peak ( Figure 4 The dotted line in the lower middle part of the figure). When glycerol is added, the oxidation peak increases significantly, while the reduction peak disappears ( Figure 4 This indicates that the Cu generated during the oxidation process 2+ It will directly oxidize glycerol (the main product is formic acid) and be reduced back to Cu + , causing the reduction peak to disappear. This indirect oxidation mechanism makes the starting potential of glycerol electrooxidation as low as 0.9 V RHE .

[0044] Comparative Example 1:

[0045] Cyclic voltammetry (from 0.36 V to RHE Sweep to 1.21 V RHE , scan rate is 0.01 V / s).

[0046] In the three-electrode system, the lattice strained CuO sample prepared in Example 1 was used as the working electrode, the graphite rod was used as the counter electrode, and the mercury / mercuric oxide reference electrode was used. An H-type electrolytic cell was used, the working electrode and the reference electrode were placed in the anode reaction chamber, the counter electrode was placed in the cathode reaction chamber, the electrolyte in the anode chamber was 15 mL of the following solution, and the electrolyte in the cathode chamber was 15 mL of 1 mol / L KOH solution. The cathode and cathode reaction chambers were separated by a Nafion proton membrane.

[0047] The reaction conditions are: 1 mol / L KOH; the solid line is 1 mol / L KOH + 0.1 mol / L glycerol, and the electrolyte volume is 15 mL. Figure 4 As shown in the upper part of the figure, at 0.85 V RHE Cu + / Cu 2+ Oxidation peak, 0.48 V RHE Cu + / Cu 2+ The reduction peak ( Figure 4 When glycerol was added, no Cu + / Cu 2+ The redox peaks changed significantly ( Figure 4 The starting potential of glycerol electrooxidation is 1.13 V. RHE .

[0048] Example 6

[0049] TEM test was performed on the samples of lattice strained CuO prepared in Example 1 before and after the reaction.

[0050] The results are as follows Figure 5 As shown, in the figure, CuO / NF-LS is the original sample (lattice strained CuO prepared in Example 1);

[0051] CuO / NF-LS-After OER is CuO / NF-LS in 1 mol / L KOH solution at 1.75 V RHE The result after 0.5 hours of reaction under potential; The above process is carried out in a three-electrode system, with the lattice strained CuO sample prepared in Example 1 as the working electrode, the graphite rod as the counter electrode, and the mercury / mercuric oxide reference electrode. An H-type electrolytic cell is used, the working electrode and the reference electrode are placed in the anode reaction chamber, the counter electrode is placed in the cathode reaction chamber, the electrolyte in the anode chamber is 15 mL of 1 mol / L KOH solution, and the electrolyte in the cathode chamber is 15 mL of 1 mol / L KOH solution. The cathode and cathode reaction chambers are separated by Nafion proton membranes.

[0052] CuO / NF-LS-After OER-Inject GLY is the result after CuO / NF-LS-After OER was immersed in 1 mol / L KOH + 0.1 mol / L glycerol solution for 0.5 h under non-electrolytic conditions.

[0053] It can be seen that after reacting in an electrolyte without glycerol, the crystallinity of the lattice strained CuO sample decreased and a large amount of amorphous appeared on the surface. After dripping glycerol for a period of time under non-electrolytic conditions, the amorphous disappeared and the crystallinity increased significantly. This shows that this indirect oxidation process may be caused by the formation of amorphous induced by stress release.

Claims

1. A method for preparing a lattice strained CuO electrocatalyst, characterized in that: In an alkaline glycerol electro-oxidation system, a Cu salt is added to the anode chamber to obtain an electrolyte containing a glycerol copper complex, and a carbon paper conductive substrate is used as an electrode. Electrolysis is performed at a given potential for a certain period of time to obtain a lattice strained CuO electrocatalyst supported on the conductive substrate. The pH of the alkaline glycerol electro-oxidation system is ≥13, and it is an alkaline aqueous solution of one or more of KOH, NaOH, and LiOH; The Cu salt is one or more of CuSO4, Cu(NO3)2, and CuCl2, and the concentration of the Cu salt is 0.03-0.05 mol / L; The concentration of glycerol in alkaline aqueous solution is 0.05~0.5 mol / L.

2. The method for preparing the lattice strained CuO electrocatalyst according to claim 1, characterized in that: The glycerol electrooxidation reaction is carried out in an H-type electrolytic cell separated by a proton exchange membrane; a three-electrode system is adopted, with the working electrode and the reference electrode placed in the anode reaction chamber, and the counter electrode placed in the cathode reaction chamber. The reference electrode is mercury / mercuric oxide, and the counter electrode is a graphite rod. Cu salt is added into the anode chamber to obtain an electrolyte containing glycerol copper complex, and the electrolyte in the cathode chamber is an alkaline aqueous solution of one or more of KOH, NaOH and LiOH with a pH value of ≥13.

3. The method for preparing the lattice strained CuO electrocatalyst according to claim 1, characterized in that: The lattice strained CuO electrocatalyst preparation process uses a constant voltage electrolysis process: the ratio of the anolyte to the working electrode area is 10-30 mL / cm 2 ; The lattice strained CuO loading on the electrode after the reaction is 0.5~10 mg·cm -2 .

4. The method for preparing the lattice strained CuO electrocatalyst according to claim 1, characterized in that: The lattice strained CuO preparation process should be carried out at 1.65~1.95 V RHE The reaction is carried out at a potential of 0.5 to 1 hour.

5. A lattice strained CuO electrocatalyst prepared by the method for preparing a lattice strained CuO electrocatalyst according to any one of claims 1 to 4.

6. Use of the lattice strained CuO electrocatalyst according to claim 5 in glycerol electrooxidation, characterized in that: The lattice strained CuO electrocatalyst electrooxidizes glycerol in an alkaline glycerol electrooxidation system.

7. The use of the lattice strained CuO electrocatalyst in glycerol electrooxidation according to claim 6, characterized in that: The initial oxidation potential of glycerol is 0.9 V RHE Lower than conventional CuO, its oxidation potential is 1.13 V RHE .